The new challenge of “exercise + X″ therapy for Duchenne muscular dystrophy—Individualized identification of exercise tolerance and precise implementation of exercise intervention - Su, Yuhui; Song, Yafeng (Frontiers in Physiology, 2022)
Duchenne muscular dystrophy (DMD) is an X-linked recessive fatal muscular disease. Gene therapy, cell therapy, and drug therapy are currently the most widely used treatments for DMD. However, many experiments on animals and humans suggested that appropriate exercise could improve the effectiveness of such precision medicine treatment, thereby improving patient’s muscle quality and function. Due to the striated muscle damage of DMD individuals, there are still many debates about whether DMD animals or patients can exercise, how to exercise, when to exercise best, and how to exercise effectively. The purpose of this review is to summarize and investigate the scientific basis and efficacy of exercise as an adjuvant therapy for DMD gene therapy, cell therapy and drug therapy, as well as to present the theoretical framework and optional strategies of “exercise + X″″ combination therapy.